A inimputabilidade penal etária como reflexo da constitucionalização garantista : uma análise das propostas de emenda à Constituição que visam a redução da maioridade penal - Matos, Êmille Laís de Oliveira (2018)
The purpose of this paper is to analyze the concept of criminal impunity under the aegis of the 1988 Federal Constitution, using the concepts of garantism and symbolic constitutionalization, as defined by Luigi Ferrajoli and Marcelo Neves, respectively. The objective is to understand the relation between these two concepts and their effects for the protection of the fundamental rights of adolescents in the context of the discussion of the lowering of the criminal majority in Brazil. This is due to the fact that the criterion of the incapacity of children under eighteen years of age has undergone several attempts to change through Proposals for Amendment to the Constitution - PECs that propose the amendment of article 228 of CF / 88. In this sense, seeking a reflexive and analytical inspiration about the debates about criminal responsibility of adolescents in the scope of Criminal and Constitutional Law, the work aims to highlight the character of the criminal responsibility as a primary and fundamental right of the adolescent, and as such, unsusceptible of being weakened or abolished through constitutional reform.